Emotional intelligence and conflictological competence in the conditions of digitalization - S. Y. Yurovitsky (Вестник университета)
In modern society, under the influence of the widespread active introduction of innovative technologies (robotization, digitalization, etc.), ordinary employees of organizations are changing. In addition, life imposes new requirements on the heads of organizations. Managers not only solve the usual tasks, but also face the problem of the need to change the usual leadership style: psychological methods are replacing directive management methods. The emotional intelligence of the manager is especially appreciated, which means the ability to observe and be aware of their own experiences and emotions of other people, manage their own feelings and emotions of another, and build interaction on this basis. Another important quality of a manager that is in demand today is conflictological competence. Robotization and digitalization prevent some traditionally arising conflicts, but new conflicts related to the virtual nature of work also arise in organizations: the rigidity and unambiguity of verbal means of communication, provoking conflict; the conflict caused by the reduction of jobs in the organization; the digital divide, which consists in differences in digital literacy and digital competence of the younger and older generations of employees.